Olympic values: The end does not justify the means - Cabrera, E. A. (Journal of Human Sport & Exercise, 2010)
Well could we shout: Gold for the victor; Zanes for scoundrels! Human beings are capable of the most beautiful acts, yet also the most despicable. Inevitably, this is also true in the world of sport, the history of which includes abundant examples of fair and foul play alike. The social responsibility of athletes who win the olive branch at an international Olympiad is such that those who are touched by the gods must consider every move they make in life. The repercussions on young athletes of their human and sporting actions are so great, they can change the course of people's lives. This is why society must think carefully about everything it does, from journalism, the fourth estate, to those leaders in education who desire a more dignified future, free of corruption. When the rules of play are broken, anywhere on the planet, humans take a step back in their evolution. Respect for the rules of the game in sport means respect for the rules of living together, respect for oneself and for one's neighbour. Education and sport should be synonyms, and sport and corruption incompatible. Adult athletes who have embraced doping are unlikely to change their ways, but the pedagogues and educators of today play a crucial role in transmitting the Olympic values of fair play. Investing in education is the best antidote to human corruption in all walks of life.